PENGARUH PEMBERDAYAAN TERHADAP PENINGKATAN KESEJAHTERAAN KELOMPOK DI DESA WISATA CARANGSARI KECAMATAN PETANG KABUPATEN BADUNG - Syntia Dewi, Ni Kadek; Supriliyani, Ni Wayan; Prabawati, Ni Putu Anik (CITIZEN CHARTER; Vol 4 No 1 (2024): Vol.4 No.1, 2024)
This research aims to investigate the extent of the influence of Empowerment on the Improvement of Community Welfare in Carangsari Village, Petang District, Badung Regency. The research method employed is quantitative method aimed at identifying the influence of empowerment (variable X) on the improvement of community welfare (variable Y) in Carangsari Village, Petang District, Badung Regency. This study uses simple linear regression as the data analysis technique. Primary data were collected through the distribution of questionnaires to 60 members of empowerment groups in Carangsari Village. The research findings indicate that empowerment has a positive impact on the improvement of community welfare in Carangsari Village. Simple linear regression analysis reveals that every 1% increase in empowerment in Carangsari Village contributes to a 59.2% increase in community welfare. Significance testing shows that the calculated t-value of 5.114 exceeds the critical t-value of 1.671 at a significance level of 0.000, indicating that empowerment has a positive and significant impact on the improvement of community welfare in Carangsari Village, Petang District, Badung Regency.Top of Form Keyword: Empowerment, Increasing Group Welfare, Carangsari Tourism Village, Petang District, Badung Regency